Ultra‐Low‐Field NMR Relaxation and Diffusion Measurements Using an Optical Magnetometer1. (31st July 2014) - Ganssle, Paul J.; Shin, Hyun D.; Seltzer, Scott J.; Bajaj, Vikram S.; Ledbetter, Micah P.; Budker, Dmitry; Knappe, Svenja; Kitching, John; Pines, Alexander
Abstract Nuclear magnetic resonance (NMR) relaxometry and diffusometry are important tools for the characterization of heterogeneous materials and porous media, with applications including medical imaging, food characterization and oil‐well logging. These methods can be extremely effective in applications where high‐resolution NMR is either unnecessary, impractical, or both, as is the case in the emerging field of portable chemical characterization. Here, we present a proof‐of‐concept experiment demonstrating the use of high‐sensitivity optical magnetometers as detectors for ultra‐low‐field NMR relaxation and diffusion measurements.